2020
DOI: 10.1039/d0tc00749h
|View full text |Cite
|
Sign up to set email alerts
|

Bright and efficient red emitting electroluminescent devices fabricated from ternary europium complexes

Abstract: [Eu(btfa)3DPEPO] and [Eu(nta)3DPEPO] are bright, red emitting complexes. They have been incorporated into single and double emitting layer electroluminescent devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…On the other hand, neutral tris(β-diketonate) complexes comprising different ancillary ligands (N^N/O^O/ N^N^N/O^O^O etc) displayed large PLQY despite their relatively short τ obs for Eu( 5 D 0 ), which implies shorter natural radiative lifetime (τ rad ) and thus could be beneficial for generating good EL performance. [7] In other words, shortening of the τ rad means that forbidden 4f-4f electronic transitions become more allowed. According to the Judd-Ofelt (JÀ O) theory, [8] the forbidden 4f-4f electronic transitions become partially allowed when the symmetry of the coordination sphere around Ln(III) is reduced and is directly related to the orbital mixing between 4f and 5d.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, neutral tris(β-diketonate) complexes comprising different ancillary ligands (N^N/O^O/ N^N^N/O^O^O etc) displayed large PLQY despite their relatively short τ obs for Eu( 5 D 0 ), which implies shorter natural radiative lifetime (τ rad ) and thus could be beneficial for generating good EL performance. [7] In other words, shortening of the τ rad means that forbidden 4f-4f electronic transitions become more allowed. According to the Judd-Ofelt (JÀ O) theory, [8] the forbidden 4f-4f electronic transitions become partially allowed when the symmetry of the coordination sphere around Ln(III) is reduced and is directly related to the orbital mixing between 4f and 5d.…”
Section: Introductionmentioning
confidence: 99%
“…Europium (Eu), the seventh element of the Ln series, is the most reactive metal, having reactivity equal to calcium and the lowest density as compared to other elements of the Ln series. Eu plays a vital role in various fields due to its luminosity, and it has been used in display technologies, biomedical science, and anticounterfeiting technology. Zhao et al found that Eu atoms having a high energy conversion rate increased the band gap of ZnO by providing additional energy levels, and thus improving the properties of ZnO. Moreover, the corrosion testing revealed that this variation in electronic structure, 9 times increased the corrosion inhibition efficiency.…”
Section: Applications and Prospects Of Ln Elementsmentioning
confidence: 99%
“…50–52 The photo- and electroluminescence of materials based on Ln complexes is adjustable through selection of the metal ion as well as the attached ligands which play a crucial role in achieving the high emission intensity through the ligand-to-metal energy-transfer process. 53–55 As a result, these materials have been found to be emissive in various parts of the UV-vis-NIR spectrum, exhibiting diverse optical features such as tunable multi-coloured luminescence, white-light emission, sensitized NIR emission, and up-conversion luminescence (UCL) that offers the conversion of NIR excitation to visible light. 56–60 These findings have provided a broad application horizon for luminescent materials based on Ln( iii ) complexes.…”
Section: Introductionmentioning
confidence: 99%